Baryon stopping probes deconfinement - Wolschin, Georg (The European physical journal. A, Hadrons and nuclei, 2016)
Stopping and baryon transport in central relativistic Pb + Pb and Au + Au collisions are reconsidered with the aim to find indications for the transition from hadronic to partonic processes. At energies reached at the CERN Super Proton Synchrotron ( sNN−−−−√=sNN= \sqrt{s_{NN}} = 6.3-17.3 GeV) and at RHIC (62.4 GeV) the fragmentation-peak positions as obtained from the data depend linearly on the beam rapidity and are in agreement with earlier results from a QCD-based approach that accounts for gluon saturation. No discontinuities in the net-proton fragmentation peak positions occur in the expected transition region from partons to hadrons at 6-10GeV. In contrast, the mean rapidity loss is predicted to depend linearly on the beam rapidity only at high energies beyond the RHIC scale. The combination of both results offers a clue for the transition from hard partonic to soft hadronic processes in baryon stopping. NICA results could corroborate these findings.